"He invited me and didn't ask anything in return" Migration and Mobility as Vulnerabilities for Sexual Exploitation among Female Adolescents in Mexico. (16th March 2017) - Rocha‐Jimenez, Teresita; Brouwer, Kimberly C.; Salazar, Marissa; Boyce, Sabrina C.; Servin, Argentina E.; Goldenberg, Shira M.; Staines‐Orozco, Hugo; Vera‐Monroy, Ricardo B.; Silverman, Jay G.
Abstract: Although human trafficking is recognized as a major human rights violation, there is limited evidence regarding the vulnerabilities that contribute to female adolescents' risk of being forced or coerced into the sex trade. Vulnerabilities such as gender‐based violence, economic and social inequalities have been shown to shape the risk of sexual exploitation among adolescents. In‐depth interviews (n=18) with current sex workers who reported being deceived or forced into the sex trade as adolescents (<17 years old) were analysed to explore their experiences of migration and mobility in Mexico. Driven by socio‐economic and vulnerabilities in home communities, adolescents often engaged in internal migration and mobility to other Mexican communities and states. Migration and mobility further predisposed them to social isolation, economic hardship and abuse, which were used as tools to trick them into the sex trade. Policies that support safer migration for adolescents in origin, transit, and destination communities are needed.